A Surface Conformal Laser‐Assisted Alloying Reaction for 3D‐Printable Solid/Liquid Biphasic Conductors. Issue 3 (3rd February 2023) - Shim, Jiyun; Kim, Yeon Uk; Kim, Young-Bin; Ji, Seul Gi; Kim, Yeon Ju; Jo, Yejin; Lee, Eun Jung; Yuk, Do-Gyeong; Lee, Su Yeon; Lee, Sun Sook; Kim, Sun-Kyung; Kim, Hyung-Seok; et al.
Abstract : Recently, electronics research has made major advances toward a new platform technology facilitating form factor‐free devices. 3D printing techniques have attracted significant attention in the context of fabricating arbitrarily shaped circuits. Herein, a 3D‐printable metallic ink comprising multidimensional eutectic gallium indium (EGaIn)/Ag hierarchical particles is proposed to fabricate arbitrarily designable solid/liquid biphasic conductors that can be inherently self‐healed/chip bonded and do not suffer from liquid flood out due to their liquid and solid nature, respectively. The EGaIn/Ag hierarchical particles are designed to have plasmonic optical absorption at the visible green–red wavelength regime, which is elucidated by an optical simulation study, and also enable the direct transfer of thermal energy, generated in the vicinity of the Ag nanoparticles, to the surface of the EGaIn particles. The 3D surface conformal green laser irradiation process activates the evolution of the biphasic conductive layer from the as‐printed insulating particulate one. The chemical/physical evolution is elucidated along with a photothermal simulation study for clarifying the suppression of undesirable side reactions. It is demonstrated that the biphasic conductors formed by successive 3D printing and the surface conformal green laser irradiation process exhibit electrical properties that have thus far been unexplored in solid metallic conductors. Abstract : Hierarchical particles comprising liquid metal particles and silver nanoparticles are designed to trigger photothermally activated interfacial alloying reactions. By subsequent direct ink writing (DIW) and green laser irradiation processes, biphasic conductors are generated on top of the 3D structure with characteristic properties that are not obtainable in conventional solid metallic features.